Urban–rural differences in outcomes and management of vertebral fractures: A real-world observational study - Chirn-Bin Chang; Rong-Sen Yang; Wei-Jia Huang; Yi-Chun Chou; Chiung-Jung Wen; Ting-Chun Huang; Ming-Chang Chen; Ding-Cheng Chan (Journal of the Formosan Medical Association, 2023)
Background: A fracture liaison services (FLSs) and its modified services reduce refractures and mortality and can be cost-effective. Limited studies have addressed whether urban–rural differences exist in vertebral fracture outcomes and management. Therefore, the aims of the study were to investigate any urban–rural differences in refracture, mortality, prescription pattern, and associated factors of vertebral fractures after receiving assistance from an FLSs. Methods: Baseline characteristics and osteoporosis medication prescription patterns of participants were collected. After 1-year follow-up, mortality, refracture rate, and osteoporosis medication switching and adherence were evaluated. Multivariate logistic regressions were performed to identify baseline correlates on one-year mortality. Results: There was higher mortality rate in the rural group but no urban–rural difference in the 1-year refracture rate after implementation of FLSs and medication management services (MMSs). The types of osteoporosis medications prescribed for both groups were similar, but participants in the rural group were less likely to change their osteoporosis medications during the 1-year follow-up timeframe and with lower adherence rate. The likelihood of being older and having chronic kidney disease, osteoarthritis, and neurological disease was higher in the rural group. Conclusion: Our multicomponent services have similar effectiveness in osteoporosis treatment between urban and rural areas. The overall adherence rate was lower in the rural group with higher mortality but no difference in the refracture rate in one year.